Escherichia coli CONTAMINATION AND ITS RESISTANCE TO ANTIBIOTICS IN SE’I MEAT - Gabryella Fransina Amalo; Trioso Purnawarman; Herwin Pisestyani (Jurnal Kedokteran Hewan, 2021)
The purpose of this study was to obtain Escherichia coli isolates from 11 se’i meat sellers in Kupang City and to observe their resistance to13 types of antibiotics. Escherichia coli were isolated and identified based on SNI 2897: 2008. Antibiotic resistance of the Escherichia colii isolates was determined using the Kirby-Bauer method. The results showed that 13 isolates (39.39%) of Escherichia coli in se’i meat samples had a high level of resistance to erythromycin (100%), tetracycline (76.92%), and doxycycline (61.54%). Isolates demonstrated increased resistance to streptomycin (46.15%), cephalothin (38.46%), trimethoprim-sulfamethoxazole (38.46%), amoxicillin (30.77%), chloramphenicol (30.77%), and choline sulfate (30.77%). The antibiotics nalidixic acid and ciprofloxacin demonstrated low Escherichia coli resistance (7.69%). Escherichia coli are sensitive to cefotaxime and gentamicin. A total of 12 isolates (92.31%) experienced MDR. The presence of non-MDR and MDR resistant Escherichia coli in se’i meat can seriously threaten community health.